A voice from the streets about Spice. (7th June 2016) - Unknown
Abstract : Ian Millar draws on personal experience of living on the streets and living and working in hostels and day care centres. He volunteers with Pathway (www.pathway.org.uk ), as part of its Expert by Experience programme, advising medical and political bodies on the healthcare of homeless people